Study of Modelling Synthetic Unit Hydograph Using ITB-1 Method (Case Study: Upstream Siak Watershed) - Mashuri, Mashuri; Kiranaratri, Ayudia Hardiayani (Jurnal Kajian Teknik Sipil, 2019)
Analysis of unmeasured flow rates in watershed with the Syntetic Hydrograph Unit (SUH) Method is the most practical and simple method. This method requires watershed characteristics as river length and watershed area. Calculation and flow rate data are very useful in the development of water resources science and civil building planning especially in water construction work. Today, the Syntetic Unit Hydrograph (SUH) Method has been widely developed and most recently the ITB-1 Syntetic Unit Hydrograph (SUH) Method. The reliability of SUH ITB-1 in Sungai Tapung Kanan and Sungai Tapung Kiri shows good performance. This is indicated by the accuracy of the volume of the Tapung Kanan River 96.30% and the accuracy of the Tapung Kiri River 99.88%. The volume control ratio / direct run off (DRO) Sungai Tapung Kanan 1,00006 and Sungai Tapung Kiri 1,000088 (close to 1). While the peak discharge produced by Tapung Kanan River is 39,950 m3/ sec and Tapung Kiri River is 38,867 m3/sec.